2005
DOI: 10.1111/j.1365-2966.2005.09057.x
|View full text |Cite
|
Sign up to set email alerts
|

Infrared mergers and infrared quasi-stellar objects with galactic winds - III. Mrk 231: an exploding young quasi-stellar object with composite outflow/broad absorption lines (and multiple expanding superbubbles)

Abstract: We present a study of outflow (OF) and broad absorption line (BAL) systems in Mrk 231, and in similar infrared (IR) quasi‐stellar objects (QSOs). This study is based mainly on one‐dimensional and two‐dimensional spectroscopy (obtained at La Palma/William Herschel Telescope, Hubble Space Telescope, International Ultraviolet Explorer, European Southern Observatory/New Technology Telescope, Kitt Peak National Observatory, Apache Point Observatory and Complejo Astronomico El Leoncito observatories) plus Hubble Spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(90 citation statements)
references
References 193 publications
(409 reference statements)
4
86
0
Order By: Relevance
“…The feature is also brighter than the expected side-lobe response. Furthermore, Mrk 231 shows evidence of distinct optical circular shell like features at a whole range of radiiresulting from a complicated pattern of outflows and winds (Lípari et al 2005). Our HCN 3−2 ring-like feature coincides with their shell feature S3.…”
Section: Integrated Intensitiesmentioning
confidence: 54%
“…The feature is also brighter than the expected side-lobe response. Furthermore, Mrk 231 shows evidence of distinct optical circular shell like features at a whole range of radiiresulting from a complicated pattern of outflows and winds (Lípari et al 2005). Our HCN 3−2 ring-like feature coincides with their shell feature S3.…”
Section: Integrated Intensitiesmentioning
confidence: 54%
“…It is possible that while radiation pressure affects the whole circumnuclear structure, winds are responsible for the highest velocity wings seen in OH. On the other hand, the high rate of mass loss derived here, together with the narrow-shell configuration favored for the HVC component, may suggest an intermittent (explosive) instead of a steady flow, consistent with the multiple, expanding, concentric supershells seen in the optical/UV at larger scales (Lípari et al 2005(Lípari et al , 2009). …”
Section: Role Of the Agnmentioning
confidence: 88%
“…While feedback processes such as superwinds in ULIRGs and starbursts have been observed for decades in lines of ionized and neutral atomic gas (e.g., Heckman et al 1990;Veilleux et al 2005;Rupke et al 2002Rupke et al , 2005aLípari et al 2005Lípari et al , 2009Spoon & Holt 2009), outflows observed in lines that trace the molecular medium are also key to understanding and quantifying this process, because the molecular phase may carry a significant or even dominant fraction of the momentum and mass outflow rates in buried stages. Far-IR spectroscopy with Herschel Space Observatory Photoconductor Array Camera and Spectrometer (PACS) (Pilbratt et al 2010;Poglitsch et al 2010) has indeed revealed powerful molecular outflows in ULIRGs traced by OH, with velocities exceeding 1000 km s −1 in some sources and mass outflow rates of several hundreds M ⊙ yr −1 (Fischer et al 2010;Sturm et al 2011;Spoon et al 2013;Veilleux et al 2013;González-Alfonso et al 2014a, hereafter GA14).…”
Section: Introductionmentioning
confidence: 99%